Natural polymeric nanofibers in transdermal drug delivery. (February 2023) - Talebi, Naimeh; Lopes, Daniela; Lopes, Joana; Macário-Soares, Ana; Dan, Aritra Kumar; Ghanbari, Roham; Kahkesh, Kaveh Hatami; Peixoto, Diana; Giram, Prabhanjan S.; Raza, Faisal; Veiga, Francisco; Sharifi, Esmaeel; et al.
Highlights: Reviewing Natural Polymeric Nanofibers in Transdermal Drug Delivery System (TDDS). Varieties of Natural-scaffolds in TDDS have been outlined. The efficacy of Natural Polymeric Nanofibers in TDDS has been elucidated. Abstract: Transdermal drug delivery systems (TDDSs) have provided many priorities over other administration routes, especially the oral route. Despite their advantages, there are some limitations regarding TDDSs, including those dedicated to the use of hydrophobic drugs. The emergence of novel nanostructures has presented various opportunities to develop advanced TDDSs to overcome the challenges on using these systems. Polymeric nanofibers present a unique structure for drug delivery applications due to their large loading capacity and ease of manipulation and functionalization. Natural-based polymeric nanofibers and synthetic polymeric nanofibers can both be used for transdermal drug delivery. Due to their favourable features, namely good biocompatibility, biodegradability, and low toxicity, natural polymeric nanofibers have attracted considerable interest over synthetic-based nanofibers. However, due to biosphere sources' scarcity and low flexibility, they are only used sparingly. Hence, the co-use of natural and synthetic polymers has been suggested to develop efficient TDDSs. So far, different methods have been proposed for polymeric nanofibers fabrication, in which electrospinning has been shown to be the most robust and flexible technique, particularly for natural polymers. This paper reviews the state-of-the art of the field of polymeric nanofibers, particularly covering TDDSs based on natural-based nanofibers. Graphical abstract: Image, graphical abstract